Carmustine as a Supplementary Therapeutic Option for Glioblastoma: A Systematic Review and Meta-Analysis - Xiao, Zhi-Ze; Wang, Ze-Fen; Lan, Tian; Huang, Wen-Hong; Zhao, Yu-Hang; Ma, Chao; Li, Zhi-Qiang (Frontiers in Neurology, 2020)
Background: Glioblastoma (GBM) is the most aggressive type of primary malignant brain tumor. Carmustine is used by intravenous injection or local implantation in the resection cavity for gliomas, including GBMs. However, the therapeutic potential of carmustine is not well recognized. This analysis aimed to evaluate the survival benefits of carmustine in glioma patients, especially those with GBM. Methods: Randomized controlled trials (RCTs) and cohort studies regarding carmustine for glioma treatment were searched in PubMed, the Cochrane Library, and Embase from January 1979 to March 2020. Quality assessment was conducted with Jadad and Newcastle-Ottawa scales (NOS). Statistical analysis was conducted by Revman 5.3 software. Results: 22 eligible RCTs and cohort studies involving 5821 glioma patients were included. Overall, glioma patients receiving carmustine as adjuvant therapy had better progression-free survival (PFS) (hazard ratio [HR]=0.85, 95% CI=0.77-0.94, P=0.002) and overall survival (OS) (HR=0.85, 95% CI=0.79-0.92, P<0.0001) than those without carmustine treatment. Subgroup analysis showed that the OS benefit was observed in GBM (HR=0.84, 95% CI=0.78-0.91, P<0.00001) but not in anaplastic glioma patients (HR=1.20, 95% CI=0.70-2.07, P=0.50). Additionally, both newly diagnosed and recurrent GBM patients who received carmustine treatment showed better OS (HR=0.86, 95% CI=0.79-0.95, P=0.002; HR=0.77, 95% CI=0.67-0.89, P=0.0002, respectively). Both carmustine implantation in resection cavity and intravenous administration significantly prolonged OS (HR=0.84, 95% CI=0.78-0.92, P<0.0001; HR=0.86, 95% CI=0.75-0.99, P=0.04, respectively). Moreover, GBM patients receiving the combined carmustine and temozolomide (TMZ) therapy had longer OS than those receiving TMZ alone (HR=0.78, 95% CI=0.63-0.97, P=0.03). Conclusion: Carmustine implantation in resection cavity provides survival benefit for GBM patients, and it may be a promising supplement to standard therapeutic protocol by offering a bridge between surgical resection and onset of TMZ therapy.